THE EFFECT OF ENDURANCE AND TIME MANAGEMENT ON PROCRASTINATION IN MEMORIZING THE QUR'AN OF STUDENTS AT LUQMANUL HAKIM IT JUNIOR HIGH SCHOOL - Lubis, Harun; Baihaqi, Ahmad; Lubis, Putri Nurhayati; Rarasati, Siti (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study aims to examine the influence of endurance and time management on the tendency of procrastination in memorizing the Qur'an among female students of SMP IT Luqmanul Hakim. Method: The approach used is quantitative with descriptive research type. The subjects in this study were female students at SMP IT Luqmanul Hakim. Data collection techniques were carried out through four methods, namely: (1) questionnaires, (2) observation, (3) interviews, and (4) documentation. Results: The results of the study showed that the level of endurance in female students was in the high category for 10 people (20%) and the medium category for 40 people (80%). For the time management aspect, as many as 10 respondents (20%) were in the high category and 40 respondents (80%) were in the medium category. Meanwhile, the level of procrastination in memorizing the Qur'an showed that 26 female students (52%) were in the high category and 24 female students (48%) were in the medium category. Novelty: Furthermore, based on the results of the hypothesis test with Product Moment correlation analysis, a significance value of 0.000 was obtained which was smaller than 0.05. This indicates that there is a significant relationship between each variable, namely endurance (X1) and time management (X2) with procrastination in memorizing the Qur'an (Y), although the level of relationship found is in the weak category.